Exploration of Entomopathogenic Nematodes in Organic Rice Field in Sleman Regency - Miftahul Ajri; Dinda Dewi Aisyah; Azizah Ridha Ulilalbab (SEAS (Sustainable Environment Agricultural Science), 2023)
Entomopathogenic nematodes (EPNs), consisting of genera Steinernema and Heterorhabditis are biological agents proven effective in killing insect pests. Organic rice fields and sandy soil textures are potential areas for exploring the presence of EPNs. This research aims to determine the diversity of genera and populations of entomopathogenic nematodes in organic rice fields in Sleman Regency. The study was conducted on organic rice fields and the UPN "Veteran" Yogyakarta Plant Protection Laboratory from July – August 2023. EPNs were obtained from Prambanan Sleman and Ngemplak Sleman, with six plots as sample units in every location. EPNs were isolated from soil samples by using Tenebri molitor larvae. The Whitehead tray method was used to isolate EPNs from the dead larvae, and the population of EPNs was counted. EPNs were identified based on the symptoms of color changes on the cuticle and morphological characters. The result showed that the cuticles of T. molitor larvae that died were blackish brown in Prambanan and Ngaliyan isolates, referred to Steinernema genera. EPNs were found in Prambanan_6, Ngaliyan_1, and Ngaliyan_2. The highest population of EPNs was on Ngaliyan_1 (38,00 EPNs/ml), and the lowest was on Prambanan_6 (2,13 EPNs/ml). Based on the morphological characters of EPNs, on the Prambanan_4, Ngaliyan_1, and Ngaliyan_2, EPNs were identified as Steinernema spp. The characteristics of Steinernema in the infective juvenile stage found are: slender body, anterior end slightly rounded and fused with the body, cylindrical stoma, no second cuticular sheath, not annulated, and conoid tail.